I am asked to evaluate the integral $$\int_{R^n}e^{-\sum_{i=1}^na_i^2x_i^2}\,dx$$ given that $a_1,a_2,\cdots,a_n$ are real numbers different from $0$.

I am clueless on how to approach this, since I have never been exposed to these types of integrals. Any help is appreciated!

  • 9
    $\begingroup$ Your integral is equal to $\prod_{i=1}^n \int_{\mathbb{R}} e^{-a_i^2x_i^2} dx_i$. $\endgroup$ – Hanul Jeon Mar 18 '18 at 8:06
  • $\begingroup$ How do you notice that? $\endgroup$ – user372003 Mar 18 '18 at 8:09
  • 4
    $\begingroup$ @user372003 It's an application of Fubini's theorem $\endgroup$ – rubik Mar 18 '18 at 9:30
  • $\begingroup$ @rubik: I mean, Fubini's theorem is not how you notice it, just how you prove that what you noticed is correct. $\endgroup$ – Mehrdad Mar 19 '18 at 2:47

By Fubini, \begin{align*} I&=\int_{{\bf{R}}^{n}}e^{-a_{1}^{2}x_{1}^{2}}\cdots e^{-a_{n}^{2}x_{n}^{2}}dx_{1}\cdots dx_{n}\\ &=\int_{{\bf{R}}}\cdots\int_{\bf{R}}e^{-a_{1}^{2}x_{1}^{2}}dx_{1}\cdots e^{-a_{n}^{2}x_{n}^{2}}dx_{n}\\ &=\left(\int_{\bf{R}}e^{-a_{1}^{2}x_{1}^{2}}dx_{1}\right)\cdots\left(\int_{{\bf{R}}}e^{-a_{n}^{2}x_{n}^{2}}dx_{n}\right)\\ &=\dfrac{\sqrt{\pi}}{|a_{1}|}\cdots\dfrac{\sqrt{\pi}}{|a_{n}|}. \end{align*}


The function is measurable because it is continuous and, also, positive. By the Fubini-Tonelli Theorem, $$ \begin{aligned}\int_{\mathbb{R}^n}\exp\left({-\sum_{i=1}^na_i^2x_i^2}\right)\,dx&=\prod_{i=1}^n\int_{\mathbb{R}}e^{-a_i^2x_i^2}\,dx_i=\prod_{i=1}^n\left(\int_{\mathbb{R}}e^{-a_i^2x^2}\,dx\right)\\&=\left(\frac{1}{|a_1\cdots a_n|}\int_{\mathbb{R}}e^{-x^2}\,dx\right)^n=\frac{(\sqrt{\pi})^n}{|a_1\cdots a_n|}. \end{aligned}$$

In case you are not familiar with the Gaussian Integral, here is a quick result.

Applying the previous theorem and a change of variable to $(\int_{\mathbb{R}}e^{-x^2}\,dx)^2\,$ we obtain $$\left(\int_{\mathbb{R}}e^{-x^2}\,dx\right)^2=\int_{\mathbb{R}}e^{-x^2}\,dx\int_{\mathbb{R}}e^{-y^2}\,dy=\int_{\mathbb{R}^2}e^{-(x^2+y^2)}\,dxdy=\int_{]0,+\infty[\times]0,2\pi[}re^{-r^2}\,drd\theta=\pi.$$ Take the square root of both sides, and the result follows.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.